2016
DOI: 10.1088/0964-1726/25/7/075028
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory alloy-based moment connections with superior self-centering properties

Abstract: Superelastic shape memory alloys (SMAs) have the potential to create a spontaneous recentering mechanism on the connections of a structural system under seismic actions, which results in mitigation of the damage in the main structural members. In this article, innovative types of steel beam-to-column moment connections incorporating SMA bolts and plates are introduced and studied through a numerical approach. First, SMA bolted end-plate connection model is produced and analyzed by means of the finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Prior research (e.g. Farmani and Ghassemieh, 2016; Yam et al, 2015) provides valuable findings on the effect of design factors on the behavior of SMA-based steel moment connections; however, the study is based on a one-factor-at-a-time (OFAT) approach. In OFAT, one factor is successively varied over its range, while the other factors are kept constant.…”
Section: Objectives Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research (e.g. Farmani and Ghassemieh, 2016; Yam et al, 2015) provides valuable findings on the effect of design factors on the behavior of SMA-based steel moment connections; however, the study is based on a one-factor-at-a-time (OFAT) approach. In OFAT, one factor is successively varied over its range, while the other factors are kept constant.…”
Section: Objectives Of This Studymentioning
confidence: 99%
“…SMAs are a special class of metallic alloys that can undergo large recoverable strains of up to 13% (Tanaka et al, 2010). SMA self-centering braced frames (Gao et al, 2016; Miller et al, 2012; Xu et al, 2016), self-centering reinforced concrete beams using SMA fibers (Shajil et al, 2013), and SMA-based steel connections (Fang et al, 2014, 2015a; Farmani and Ghassemieh, 2016; Wang et al, 2017) are examples of research on the applications of SMA materials in earthquake-resistant structures.…”
Section: Introductionmentioning
confidence: 99%
“…Straight SMA fiber is seldom used because it only has frictional resistance, which is too weak in comparison with anchorage resistance [ 30 , 31 , 32 ]. Previous studies have suggested various shapes of SMA fibers, such as L-, N-, dog-bone, and paddle-shaped ones [ 33 , 34 , 35 , 36 ]. Of these types, the paddled SMA fiber is the most effective to provide end-anchoring action, and thus it is the most appropriate for crack-bridging [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the conventional bracing damper system has an excellent ability not only to absorb the external impact but also to diminish the structural vibration, it has the disadvantage of requiring additional maintenance due to the residual deformation caused by the lack of recentering capability [10][11][12][13][14]. Accordingly, this paper proposes new bracing damper systems that can e ectively reduce the residual displacement by installing seismic retro t devices to enhance the recentering capability of the bracing member.…”
Section: Introductionmentioning
confidence: 99%